Pola Asuh Islami dalam Al-Qur’an: Kajian Kontekstual Terhadap Tantangan Pendidikan Anak di Era Digital - Mhd Abror; M Kiman; Hidayatullah Ismail (Universitas Islam Lamongan, 2025)
The rapid advancement of technology today presents significant new challenges across various aspects of life, particularly in the field of child education. Easy access to information through the internet and social media makes children increasingly vulnerable to exposure to negative content that can erode their moral and ethical values. In this context, an appropriate parenting model becomes crucial in safeguarding and shaping children's character in accordance with noble values. This study aims to examine the relevance of Islamic parenting principles found in the Qur’an in relation to the contemporary challenges faced by Muslim families in the digital era. The research employs a library research method using a thematic interpretation (tafsīr maudhū‘ī) approach to explore Qur'anic verses related to parenting. The findings indicate that Islamic parenting principles—such as role modeling, monotheism (tauhid), effective communication, social control, and compassion—hold strong relevance in addressing modern-day challenges. Although parenting methods may evolve in form to suit the current context, the essence of Qur’anic values must be preserved as a foundational guide in educating children amidst the complex realities of the digital age.